PUBLIC DOMAIN PROTECTION. USES AND REUSES OF PUBLIC DOMAIN WORKS - Monica Adriana LUPAȘCU (Challenges of the Knowledge Society, 2015)
This study tries to highlight the necessity of an awareness of the right of access to the public domain, particularly using the example of works whose protection period has expired, as well as the ones which the law considers to be excluded from protection. Such works are used not only by large libraries from around the world, but also by rights holders, via different means of use, including incorporations into original works or adaptations. However, the reuse that follows these uses often only remains at the level of concept, as the notion of the public’s right of access to public domain works is not substantiated, nor is the notion of the correct or legal use of such works.